2021
DOI: 10.1016/j.redox.2021.101982
|View full text |Cite
|
Sign up to set email alerts
|

Decreased availability of nitric oxide and hydrogen sulfide is a hallmark of COVID-19

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is involved in a global outbreak affecting millions of people who manifest a variety of symptoms. Coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 is increasingly associated with cardiovascular complications requiring hospitalizations; however, the mechanisms underlying these complications remain unknown. Nitric oxide (NO) and hydrogen sulfide (H 2 S) are gasotransmitters that regulate key ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 45 publications
5
54
4
1
Order By: Relevance
“…Quite a few literatures have suggested that NO exerts its pathophysiological function mainly via S-nitrosylation, instead of via other pathways as shown in Scheme 2 . In one recent study by Dominic et al, S-nitrosothiol was significantly lower in the COVID-19 patients than in the control group [ 36 ]. It indicated that blood SNO levels changed during SARS-CoV-2 infection with uncovered mechanism yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quite a few literatures have suggested that NO exerts its pathophysiological function mainly via S-nitrosylation, instead of via other pathways as shown in Scheme 2 . In one recent study by Dominic et al, S-nitrosothiol was significantly lower in the COVID-19 patients than in the control group [ 36 ]. It indicated that blood SNO levels changed during SARS-CoV-2 infection with uncovered mechanism yet.…”
Section: Discussionmentioning
confidence: 99%
“…However, conversely, in several reports, decreased basal NO production or bioavailability (normally in the 100–400 nM range) has been suggested to underlie elevated apoptosis of endothelial cells induced by SARS-CoV-2 infection, increased inflammation, or excessive reactive oxygen species (ROS) [ 23 , 24 , 35 ]. One recent study reported decreased total NO, nitrite and SNO in COVID-19 patients in hospital [ 36 ]. Another study in Spain showed that nitric oxide diffusion was reduced in around 40% patients discharged from hospital, via respiratory function tests with a MasterScreen PFT equipment [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Survivors reportedly exhibit higher serum levels of H 2 S and higher numbers of circulating lymphocytes ( 70 ); H 2 S stimulates T cell proliferation ( 71 ). Indeed, exogenous H 2 S therapy may be beneficial in mild to moderate COVID-19 disease ( 72 ).…”
Section: Elevated Levels Of Prooxidants In Covid-19 and Me/cfsmentioning
confidence: 99%
“…However, in aged individuals and those with cardiovascular disease such as diabetes and hypertension, the 2 most prevalent comorbidities in COVID-19, homeostatic endothelial functions become impaired ( 22 ). Clinical studies provide evidence that endothelial dysfunction is a major determinant of severe COVID-19, and patients have markers of endothelial injury, including increased levels of fibrinogen, fibrin degradation products, D-dimer, von Willebrand factor ( 23 , 24 ), and soluble thrombomodulin ( 15 ), as well as signatures of impaired endothelial function such as apoptotic ECs ( 17 ), decreased nitric oxide availability ( 25 ), and vascular leakage ( 26 ).…”
Section: Introductionmentioning
confidence: 99%